Pembahasan ilmu al Qur'an - Mana'ul Quthan (Rineka Cipta, 1993)
ir,jil.1,c.1-5; jil.2,c.1-7/tr, jil. 1=c.6/Oen, jil.2,c.8/oen, jil.2,c.9/oen, jil.1=c.7/tr, jil.1=c.8-9/tr, jil.2=c.10/nr,jil.2=.21/ng,jl1=1/nr,jil.1=.23